Logistics service innovation management - evidence from two longitudinal case studies at Deutsche Post - Kohler, Thomas (Cranfield University, 2005)
This study aims at exploring ways to better manage organisational development and change in practice. For project managers like myself it is important to gain a solid understanding about the drivers or inhibitors in these developments and change processes. I was particularly interested in those development and change processes aimed at the achievement or maintenance of competitive advantage within an industry. One way of achieving or maintaining competitive advantage may be based on serving the customer’s strategic needs through innovation (Chapman et. al., 2003). Various process models propose how service innovation projects in general should be managed. However, large and mature organisations in particular may encounter difficulties in their implementation (Dougherty and Hardy, 1996). From a practitioner’s point of view, this is an especially dire situation as service innovations, particularly those driven by strategic intent, are under great pressure from decision-makers to succeed. Along these lines Dougherty (1996) suggests a shift of focus, to a focus on the fact that innovation activities have inherent ‘tensions’. She defines ‘tensions’ as challenges that have to be dealt with during an innovation project. Drawing on the evidence of three sequential projects conducted at DHL Express, the parcel branch of Deutsche Post, I tried to investigate the nature of service innovations and their inherent tensions. By longitudinally tracking the activities and their inherent tension’s life cycle in an exploratory case study, I tried to get a better understanding of how tensions appear in innovation projects, as well as the dynamics of these tensions. The evidence of this first case study was used to theorise about an optimised sequence of activities, as well as first propositions about how tensions might be managed. The first set of propositions derived from the exploratory case was then given a trial in a second longitudinal case study. The activities of the first logistics service innovation project included a major ‘information engineering’ component. According to Davenport (1993) ‘information engineering’ deals with description of an already conceptualised process in informational terms, such that a system can be rapidly and rigorously constructed to support the new process design. Hence, the set of activities proposed in this study include the capability to include an information system component as a service innovation deliverable; a capability long recognised to be essential for exhorting positive influences on the operation of logistics systems (Kent, 1996). This research was conducted in the context of a number of unusual opportunities. First and foremost, both case studies had similar stakeholders and objectives. Secondly, all stakeholders contributing to the first case study were willing and able to collaboratively contribute to improvements in the management of activities and their inherent tensions. Finally, all inquiry participants then implemented those propositions into the following case study for inspection. Based on the evidence of the second case study, I show how managing activities and tensions with congenerous dedication exploited all four tensions to improve the probability of innovation projects to deliver.